Rapid microwave synthesis of fluorescent hydrophobic carbon dots - Mitra, Shouvik; Chandra, Sourov; Kundu, Tanay; Banerjee, Rahul; Pramanik, Panchanan; Goswami, Arunava (RSC Advances, 2012)
Fluorescent hydrophobic carbon dots (HCDs) have been fabricated from a poloxamer by a simple microwave assisted process within a few minutes for the first time. Small and distinct spherical HCDs emitted bright blue and green fluorescent light depending upon the excitation wavelength and were dispersed easily in a wide variety of organic solvents. HCDs exhibited excellent water resistant behavior with a contact angle of similar to 122 degrees enforcing good hydrophobic character which will be quite useful in potential surface applications.

Reversible phase transformation in proton conducting strandberg-type POM based metal organic material - Dey, Chandan; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
A Cu(II)-phenanthroline connected Strandberg-type polyoxometalate based proton conducting MOF, Cu3Mo5P2, that contains one dimensional parallel water channels has been reported. Cu3Mo5P2 shows proton conduction at room temperature as well as elevated temperature.

Relating pore hydrophilicity with vapour adsorption capacity in a series of amino acid based metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (CrystEngComm, 2013)
A new Zn based porous homochiral metal-organic framework, ThrZnOAc, belonging to unh topology, has been synthesized using pyridyl functionalized threonine and Zn(OAc)(2) as the metal precursor. Stepwise substitution of the homochiral MOF backbone by simply changing the sidearm of the amino acids (isopropyl in the case of valine, methyl in alanine and hydroxyethyl in threonine) resulted in increased water adsorption in ThrZnOAc compared to the previously reported ValZnOAc/AlaZnOAc. Extensive solvent sorption isotherms (water, methanol, isopropanol and toluene) have been carried out, which revealed high solvophilic interaction with polar solvents in ThrZnOAc due to the polar pore [2-hydroxyethyl {-CH(OH)CH3} sidearm of the amino acid], which is not prominent in the corresponding valine/alanine counterparts. The aforementioned functionalization in a series of isostructural amino acid based MOFs with the only difference being in the sidearm and their emergence as enhanced solvophilic materials is unprecedented in the MOF literature.